PENGARUH PEMBERIAN RANSUM PABRIK DENGAN PENAMBAHAN DAUN PEPAYA DAN DEDAK PADI TERHADAP INCOME OVER FEED COST (IOFC) AYAM KAMPUNG SUPER - Nanda Agustian, Wira; Yani, Ahmad; Amrullah, Amrullah; Budiman, Cecep; Hamdani, Asrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Super native chicken is a cross between native chicken and laying hen. Super native chicken requires nutritious feed to obtain optimal production results. This study aims to determine the effect of providing factory rations with the addition of papaya leaves and rice bran on income over feed cost (IOFC) in super native chicken. The study was conducted from January 2026 to March 2026 using a completely randomized design with 5 treatments and 4 replications. Data analysis was carried out through analysis of revenue, feed costs and income over feed cost (IOFC) using analysis of variance Completely Randomized Design (CRD). The results showed that all research variables such as revenue, feed costs and income over feed cost (IOFC) had the highest average value, namely in treatment P0 with Factory Ration 50% + (100% papaya leaves + 0% rice bran) with an average revenue value ranging from Rp. Rp. 28,406-Rp. 37,183, feed costs Rp. Rp. 690-2,669, and the average income over feed cost (IOFC) ranged from Rp26,734-Rp34,913.